Assessment and classification of peripheral pain in athletes: a scoping review protocol - Purcell, C.; Duignan, C.; Fullen, B.; Caulfield, B. (BMJ Open Sport & Exercise Medicine, 2021)
Pain is often presumed to be part of the sport injury experience. The time-loss definition of injury leads to under-reported athletic pain impacting performance and quality of life. Whilst research regarding the assessment and classification of back pain in athletes is emerging, little has been reported regarding how peripheral pain is assessed and classified in research and practice. Six databases will be searched for relevant articles. Title and abstract screening followed by full-text screening will be completed by two independent reviewers. Data charting will be carried out using a modified standardised form. Descriptive results and frequencies will be reported. Pain measures identified in the studies will be mapped against the IOC Athlete Pain Framework alongside a narrative summary. Published peer-reviewed primary research studies alongside systematic reviews and clinical practice guidelines reporting the assessment or classification of pain in athletes of any age with chronic or acute peripheral pain across all study contexts in the English language on human participants from inception of the databases will be included. The results of this study are part of a body of research which will be used to inform the development of a pain assessment framework. The scoping review will be submitted for peer-reviewed journal publication and presented at sports medicine conferences. This review will inform researchers and clinicians working with athletes in pain how pain assessment and classification is currently conducted and positioned against the IOC Athlete Pain Framework.